Kajian Kehandalan Teknologi Irigasi Air Tanah untuk Usaha Tani Sistem Sorjan di Kabupaten Kulonprogo - Muhjidin Mawardi (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2003)
A technology of ground water irrigation for sorjan farming system has been applied by farmers in Kecamatan Panjatan, Kabupaten Kulonprogo for years. The technology is simple and indigenous but there is no such infOrmation concerning it reliability and appropriateness. The aims of the study are to examine the reliability of the ground water irrigation for soda', farming Spiem and factors influence performance of the technology. The reliability is examined by the productivity of land and waler use, irrigation effectiveness and farmers income from the sorjan farming system. The study is conducted by survey and field observation method, includes physical characteristics of the sorjan land, ground water level, interval of wells ernd cropping pattern. Labour used for irrigation perday, time consumed for one irrigation, irrigation capacity perday and irrigation effectiveness are observed in the field during the working days. Crops production and irrigation cost, crops yield and famers income from sorjan farming are investigated through field survey. Two locations of sorjan farming are selected as the the sample locations for the study. The study concludes that the sorjan farming under crops rotation of rice and vegetable in the furrows and vegetable crops for all season on the ridges performs as a productive and adaptive land and water use for agriculture. The technology of ground water irrigation for the sorjan farming is considered as a reliable technology from the point view of adaptability to the local environment, water availability, irrigation effectiveness and farmers income per year from sorjan farming . Besides that. the technology is developed by the local farmers based on their wise and experiences to local circumstances and therefore, more appropriate and sustainable.